Desafios éticos da empresa como expressão da quarta dimensão dos direitos humanos - Ribeiro, Elenice Baleeiro Nascimento (2015)
This dissertation aims to analyse the link between companies and the observance of ethical standards. The issue explored in this dissertation wonders if ethics would represent a new value under which would be raising another dimension of human rights, the fourth, and if this value would now be required in business activities. It starts with the theory of dinamogenesis of human rights focusing the analyses of the exercise of power as the trigger of the demands that leads to the establishment of rights of, liberty, equality and fraternity/solidarity, proclaimed at the speech do Karel Vasak (1979). After that, is analysed the raising of a new dimension of human rights, based on ethics to confront the demands stated by economy globalization, revolution in information technology and in biogenetics. This study also explores the analysis of sustainability recommended in the Brundtland Commission Report (1987 – UN) and its dissemination to the corporative scope, through the observance of the 'tripple bottom line' which links the company's perpetuation with respect for the environmenteconomic efficiency and impact of their activities on society. Is still analysed the functionalization of the Law related to the companies, observing the social e solidary function dictated constitutionally, exploring the relation of the company with ethics as a function. After clarifying internal institutes of the brazillian constitution (such as the Bankruptcy Law – Law 11,101/05 and the Law of Solid Waste National Policy – Law 12,305/10), which exemplify the legal guarantee of the social function and solidarity dictated constitutionally, It moves to the analysis of corporate governance in its relation to ethics, approaching the inclusion of prescribed tools in this institute, such as compliance and Code of Ethics in Corporate Law – Law 6,404/76 and Anti-Corruption Law – Law 12,846/13; which confirms the hypothesis raised that the business activity has been suffering demands of ethic nature, which is already justifying the enactment of laws under which such value is present. It started from literature supported by the hypothetical deductive method and literature review for research aiming to analyze and answer the question posed.